2010
DOI: 10.1243/13506501jet745
|View full text |Cite
|
Sign up to set email alerts
|

Elastohydrodynamic lubrication analysis of metal-on-metal hip implants with complex structures using the finite-element method

Abstract: Various complex structures are employed in different metal-on-metal (MOM) hip prostheses for different purposes. For the elastohydrodynamic lubrication (EHL) study of these prostheses, the elastic deformation calculation is not a trivial task due to the effect of complex structures. The finite-element method (FEM) is an attractive approach for solving these problems because of its flexibility in handling complex geometries. Moreover, the availability of high-level ready-to-use finite-element commercial softwar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…A significant amount of research has been undertaken on the EHL of artificial hip joints . In these models, the interaction of the fluid film pressure and the elastically deformable head and cup is calculated to predict both the film thickness and the lubricating fluid pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant amount of research has been undertaken on the EHL of artificial hip joints . In these models, the interaction of the fluid film pressure and the elastically deformable head and cup is calculated to predict both the film thickness and the lubricating fluid pressure.…”
Section: Introductionmentioning
confidence: 99%
“…A significant amount of research has been undertaken on the EHL of artificial hip joints. [1][2][3][4][5][6][7][8][9][10][11][12][13] In these models, the interaction of the fluid film pressure and the elastically deformable head and cup is calculated to predict both the film thickness and the lubricating fluid pressure. Such studies have shown that the fluid-filled lubricating gap is at nanometer size-an extremely small gap when compared to typical engineering bearing problems, where the fluid-filled gap is typically in a range of 1-100 mm.…”
Section: Introductionmentioning
confidence: 99%
“…The diameter, radial clearance and cup thickness of this surface hip prosthesis were 50 mm, 75 mm and 3.94 mm, respectively. 23 The minimum and maximum thicknesses of the head were 2.5 and 9 mm, respectively. The radius and length of the pin of the head were approximately 3.5 and 60 mm, respectively.…”
Section: Full Modelmentioning
confidence: 92%
“…19 The current EHL models applicable to hip replacements can be found in a few review articles. 19,20 Although a large number of lubrication studies have been performed for THRs, 20 only few studies [21][22][23] have been performed to investigate how design parameters, such as the head diameter, diametric clearance, cup wall thickness and detailed structures and fixation of the femoral component, affect the EHL of MOM hip resurfacing prostheses. These studies assumed that the cup was horizontally positioned and the head was vertically positioned.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation